Characterisation of the properties of a negative hydrogen ion beam by several beam diagnostic techniques. (25th May 2016) - Maurizio, R.; Fantz, U.; Bonomo, F.; Serianni, G.
Abstract: The beam properties of the BATMAN negative ion source, which is the prototype of one module of the source for the ITER neutral beam injection system, are characterised by means of three diagnostic techniques: beam emission spectroscopy (BES), the experimental calorimeter mini-STRIKE and a copper calorimeter. The main beam parameters—beam divergence, homogeneity and top–bottom asymmetries—are studied in different operational scenarios: with different magnetic filter field setups, source settings and with different gases (hydrogen or deuterium). Among all dependences, the influence of the magnetic field configuration on the beam and the evolution of the beam features during some conditioning days are investigated in detail. Data show that the stronger the filter field in the beam region, the higher the beam top–bottom asymmetry—likely a v × B effect. During the conditioning of the source, such vertical beam asymmetry increases as well, suggesting an inhomogeneous H − production at the first grid of the extraction system.